DECREASED ENZYME ACTIVITIES OF CHAPERONES PDI AND BIP IN AGED MOUSE LIVERS - Nuss, Jonathan E. (2007)
The endoplasmic reticulum (ER) is a target for endogenously generated reactive oxygen species (ROS) during aging. We have previously shown that the ER chaperones, protein disulfide isomerase (PDI) and immunoglobulin heavy chain binding protein (BiP) are oxidatively modified within the livers of aged mice. In this study we assess the functional consequences of the age-dependent oxidation of these two proteins. Specific activity measurements, performed on purified protein samples obtained from young and aged mouse livers, show definitive decreases in BiP ATPase activity and dramatic reductions in PDI enzymatic activity with age. Overall, these results suggest that protein folding and other activities mediated through PDI and BiP are diminished during aging. Furthermore, the relative loss of these chaperone-like activities could directly contribute to the age-dependent accumulation of misfolded proteins, a characteristic of the aging phenotype.